Congenital Uterine Anomalies and Pregnancy Outcomes: A Population-Based Retrospective Cohort Study - Ahyoung Choi; Min-A Kim; Geum Joon Cho; Han Sung Hwang (Journal of Clinical Medicine, 2026)
Background/Objectives: Congenital uterine anomalies (CUAs) are associated with adverse pregnancy outcomes, but large-scale data, particularly in Asian populations, remain limited. We evaluated obstetric and neonatal outcomes in women with CUAs using a large national Korean cohort. Methods: This population-based retrospective cohort study used the Korean National Health Insurance Service database and included 878,000 singleton deliveries between 2018 and 2023. CUAs were identified using International Classification of Disease, 10th Revision (ICD-10) codes and categorized as double, septate, bicornuate, or unicornuate uterus. Outcomes were compared with women without CUA using multivariable logistic regression adjusted for maternal age, parity, chronic hypertension, and pregestational diabetes mellitus. Results: CUAs were identified in 6038 women (0.68%), most commonly double uterus. Risks were higher for Cesarean delivery (adjusted odds ratio [aOR] 2.57, 95% confident interval [CI] 2.38–2.77), breech presentation (6.42, 5.91–6.99), placenta previa (1.79, 1.45–2.22), and placental abruption (3.01, 2.26–4.01). Neonates were more likely to be preterm (2.43, 2.10–2.80), small for gestational age (1.90, 1.70–2.10), and to experience respiratory distress syndrome (2.04, 1.63–2.55) and intraventricular hemorrhage (3.04, 2.00–4.62). Conclusions: CUAs are associated with increased risks of adverse obstetric and neonatal outcomes, with subtype-specific variations, warranting tailored prenatal counseling and management.